Pengembangan Buku Cerita Bergambar Berdasarkan Lagu–Lagu Berbahasa Jawa sebagai Media Penanaman Nilai Karakter Anak Usia Dini di Kabupaten Pemalang - Wati, Ira Pergiwo; Sukoyo, Joko; Widodo, Widodo (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Character education is very important, especially in childhood is an effective time for initiating the introduction and construction of traditional art. Based on observation, researchers found the problem, which is the lack of availability of the media that is able to attract the interest of students in learning Java language songs. Besides, children don’t understand Javanese Songs. The researchers had the idea to try to develop an interesting book, creative and innovative that is picture storybook based on Javanese language songs as a media to offer value character for children. In addition, that book can be used as cultural preservation efforts through appreciation. This is research and development (R&D). The data collection techniques used were documentation, observation, and question form. This book contains two main characters, there are safeguarding the environment and independently. This book contains 22 pages and it developed two stories containing character values.